Natural and anthropogenic factors affecting Allegheny woodrat occupancy. (29th October 2018) - Lombardi, Jason V.; Castleberry, Steven B.; Mengak, Michael T.; Terrell, V. K.
ABSTRACT: The Allegheny woodrat ( Neotoma magister ) is a habitat specialist closely associated with rock habitats throughout the Appalachian region. Although genetic studies have examined gene flow and connectivity among rock habitats, estimates of initial occupancy, colonization, and local extinction based on field studies are not available. Therefore, we used data from camera surveys to examine site and landscape characteristics with the potential to influence Allegheny woodrat initial occupancy, colonization, and local extinction at Shenandoah National Park, Virginia, USA, from May to September 2015. We modeled these parameters relative to covariates using a multiseason occupancy modeling approach. We found that colonization of rock outcrops by Allegheny woodrats occurs across a range of human impact levels, supporting previous research that Allegheny woodrats are relatively tolerant of human disturbance, including the type of disturbances (e.g., rock climbing, hiking) that occur at rock outcrops on our study area and other protected areas within the range. We also found lower localized extinction rates in oak ( Quercus spp.)–hickory ( Carya spp.) than oak–pine ( Pinus spp.) forests, likely because the diversity of mast‐producing species and abundant understory vegetation in oak–hickory forests provide habitat conditions more conducive to woodrat persistence. Management efforts for Allegheny woodrats should focus on maintaining forests with a diversity of mast‐producing species, which could include use of prescribed fire and monitoring and treatment programs to reduce effects of invasive insects and pathogens. © 2018 The Wildlife Society. Abstract : We sought to identify landscape and site characteristics with the potential to influence Allegheny woodrat initial occupancy, colonization, and local extinction at Shenandoah National Park, Virginia, USA. We determined that colonization of rock outcrops by Allegheny woodrats occurs across a range of human impact levels and localized extinction rates were lower in oak–hickory than oak–pine forests.